Change of gait in patients with lateral osteoarthritis of the knee after mobile-bearing unicompartmental knee arthroplasty - Seeger, Jörn Bengt; Schikschneit, Janina Patricia; Schuld, Christian; Rupp, Rüdiger; Jäger, Sebastian (Knee surgery, sports traumatology, arthroscopy, 2015)
Purpose Patients with lateral osteoarthritis of the knee suffer not only from pain but also impaired gait and limited mobility. Common treatment options are total knee replacement and lateral unicompartmental knee arthroplasty (UKA). The domed lateral mobile-bearing Oxford Uni is a new treatment option for patients with isolated osteoarthritis of the lateral compartment of the knee joint. We used instrumented gait analysis and clinical scores to study patients before and after lateral UKA.MethodsNineteen patients suffering from lateral osteoarthritis underwent implantation of a mobile-bearing lateral UKA. They were examined in a gait analysis before the operation and after an average follow-up time of 7 months. Gait analysis was performed on a treadmill with six infrared cameras to identify gait characteristics (e.g. velocity, stride time, stride length, knee abduction or hip adduction).ResultsMean velocity changed from 0.58 to 0.73 m/s. Significant advancements were also found in knee abduction and hip adduction. Time and length of strides improved significantly as well as the clinical scores American Knee Society Score, Oxford-12, FFb-H-OA and Devane Score.ConclusionPatients with lateral osteoarthritis of the knee showed an impaired gait with an increased knee abduction and hip adduction angle. Implantation of a lateral mobile UKA can restore normal axis of the leg and improve gait and function of the knee. Instrumented gait analysis is a suitable measuring instrument to quantify and qualify the post-operative change of gait.Level of evidenceII.
Gesehen am 07.04.2017